Kinerja Panel Surya dengan Pelacak Matahari Dual Aksis menggunakan Algoritma berbasis Sensor LDR - Bernadeta Wuri Harini; Petrus Setyo Prabowo; Yehezkiel Krisma (LPPM Universitas Putera Batam, 2022)
One source of renewable energy is solar energy. The main component in a solar energy system is the solar panel. To maximize the amount of sunlight harvested by the solar panels, the panels need to track the position of the sun. In this study, a dual-axis tracker is used in the form of a tip-tilt dual-axis tracker. The drivers used are two DC motors equipped with a gear box. The algorithm used is an LDR sensor output based algorithm. Solar panels equipped with solar trackers, even with a simple algorithm using LDR output values, can improve the performance of solar panels. The current generated by a solar panel with a solar tracker is higher than when the solar panel is in a static position. The current difference in the two conditions is the smallest of 16.17 mA and the largest of 544.01 mA. When using a solar tracker, the output power of the solar panel is more than 5.32 W, while when it is fixed, the power of the solar panel is small, even reaching 0.25 W. The output voltage of the solar panel is more than 13 V, while when it is fixed, the voltage of the solar panel is drops to below 13 V, which is 12.81 V.